Assessment of Host Defence Mechanisms Induced by Candida Species. (July 2013) - Paoletti, I.; Fusco, A.; Grimaldi, E.; Perillo, L.; Coretti, L.; Di Domenico, M.; Cozza, V.; Lucchese, A.; Contaldo, M.; Serpico, R.; Guida, A.; Donnarumma, G.
Some species of Candida are opportunistic pathogens that can cause disease in a host immunocompromised by underlying local or systemic pathological processes. C. albicans is the species most often associated with oral lesions, but other species of Candida, including C. glabrata, C. tropicalis and C. parapsilosis, have also been isolated in the saliva of subjects with and without candidiasis. In the present study we evaluated the host defence mechanisms induced by Candida albicans and other Candida species in monocytes and oral epithelial cells in order to establish the existence of a species-specific cellular response. Our results indicated that, during Candida species infection, the epithelial cells actively participate in the host defence by producing antimicrobial peptides and proinflammatory cytokines. Moreover, in infections caused by Candida tropicalis and Candida glabrata, the host defence may be strengthened by the release of perforin and granzyme by polymorphonuclear leukocytes recruited at the site of infection.